Pathophysiological Aspects of COVID-19-Associated Vasculopathic Diseases - Greistorfer, Thiemo; Jud, Philipp (Thrombosis and Haemostasis, 2023)
Since the beginning of coronavirus disease 2019 (COVID-19) pandemic, numerous data reported potential effects on the cardiovascular system due to infection by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), which may lead to COVID-19-associated vasculopathies during the acute phase and measurable vascular changes in the convalescent phase. Infection by SARS-CoV-2 seems to have specific direct and indirect effects on the endothelium, immune and coagulation systems thus promoting endothelial dysfunction, immunothrombosis, and formation of neutrophil extracellular traps although the exact mechanisms still need to be elucidated. This review represents a recent update of pathophysiological pathways of the respective three major mechanisms contributing to COVID-19 vasculopathies and vascular changes and includes clinical implications and significance of outcome data.
Keywords: COVID-19; endothelial dysfunction; coagulation; immune system; immunothrombosis; neutrophil extracellular traps